Field Philosophy as a Disruptive Practice: Between Philosophical Legitimacy and Methodological Divergence - Adou Josias Nyamike (European Scientific Journal, ESJ, 2026)
Philosophy is increasingly confronted with demands for social relevance that challenge its traditional modes of intervention. This article critically examines field philosophy as a situated and dialogical practice developed with non-academic actors. Drawing on Frodeman, Vollaire, Despret, and Stengers, it argues that field philosophy is not merely an applied extension of philosophy nor a transposition of social science methods. Rather, it reconfigures philosophical practice at methodological and epistemic levels. While it shares an attention to concrete situations with empirical inquiry, it differs through its reflexive stance, its normative orientation, and its commitment to co-construction rather than explanation. By foregrounding post-research follow-up and the empowerment of actors, the article proposes recognizing field philosophy as a disruptive yet legitimate practice that reshapes the public and epistemic responsibilities of philosophy.